Application of Team Assisted Individualization Cooperative Learning to Improve Mathematics Learning Multiplication Material - Nurkholidah Nurkholidah (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve the multiplication material learning Mathematics. This study uses the Team Assisted Individualized Cooperative learning model, namely by grouping students into several groups, each of which contains smart children and less intelligent children. Each group worked on the multiplication questions given by the teacher, children who were good at guiding children who were less intelligent (peer tutors). The results of the study using this learning model showed encouraging results for children who previously had many who were incomplete by using this learning model many children who value above KKM.